Response of Porang (Amorphophallus muelleri) to the Application of Arbuscular Mycorrhizal Fungi - Zuliyan Agus Nur Muchlis Majid; Novianti Adi Rohmanna; Linda Rahmawati; Sri Devi (Institut Pertanian Bogor, 2026)
Arbuscular mycorrhizal fungi (AMF) are fungi that create symbiotic relationships with plant roots, enhance nutrient absorption, and aid in root growth initiation. The purpose of this study is to evaluate how porang plants (Amorphophallus muelleri) respond to AMF delivery at various doses. The study utilized a Completely Randomized Design with five treatments: MKK0 (control), MKK1 (15 g AMF/10 kg soil), MKK2 (25 g AMF/10 kg soil), MKK3 (35 g AMF/10 kg soil), and MKK4 (45 g AMF/10 kg soil). The characteristics measured were plant height, plant dry weight, and tuber weight. The results revealed that the MKK1 treatment produced the optimum response to the plant height of 40.75 cm, dry weight of 6.3 g, and tuber weight of 26.5 g. AMF at a dose of 15 g significantly boosted the growth and expansion of porang tubers. Due to the soil's low nutrient availability, excessive AMF doses did not produce desirable outcomes. Thus, administering the appropriate dose of AMF can promote proper porang development. Keywords: Amorphophallus muelleri, arbuscular mycorrhizal fungi, optimal dosage